Soil and Plant Enzymes Responses to Zinc Oxide Nanoparticles in Submerged Rice (Oryza sativa L.) Ecosystem - Srivastav, Akansha; Shukla, Anurakti; Singhal, Rakesh Kumar; Srivastav, Sudhakar; Ganjewala, Deepak; Shrivastava, Manoj (Trends in Sciences, 2023)
In the present study, the effects of zinc oxide nanoparticles (ZnO NPs) on rice (Oryza sativa L. cv. PB1509) plant growth were assessed in hydroponics (5, 10, 25, 50 mg L−1) and soil microcosm (5, 10, 25 50 mg kg−1) experiments. In both hydroponics and soil experiments, Zinc (Zn) accumulation in plant parts (roots, shoots and grains) was found to increase with increasing doses of ZnO NPs. Grains accumulated 29 mg kg−1 Zn at 50 mg kg−1 ZnO NPs in the soil experiment. In the hydroponics experiment, growth and photosynthetic pigments were induced by ZnO NPs up to 10 mg L−1, while higher doses of 25 and 50 mg L−1 were toxic to plant growth. Antioxidant enzyme activities (SOD, CAT, APX and GPX) were mostly increased or unaffected by all ZnO NPs doses. In soil experiments, acid and alkaline phosphatase activities were increased at 5 mg kg−1 followed by a declining trend. However, a significant decrease occurred only at 50 mg kg−1. Urease activity in soil was significantly increased at all doses of ZnO NPs, while the activity of dehydrogenase did not show any significant change up to 25 mg kg−1. The length of plants and photosynthetic pigments did not show much toxicity except root length beyond 10 mg kg−1; however, the biomass of plants including grains was significantly lower than control beyond 5 mg kg−1 dose. The activity of antioxidant enzymes (GPX, APX and CAT) showed a significant increase at all doses of ZnO NPs. The DTPA extractable Zn concentration in the soil was significantly elevated with increasing exposure concentrations of ZnO NPs. Based on hydroponics and soil experiments, this study suggests a dose of up to 10 mg L−1 or 10 mg kg−1 would be an appropriate dose for augmenting the growth of rice plants and Zn accumulation, and this can be practically utilized for rice plants growing in submerged conditions. HIGHLIGHTS Rice plants exposed to ZnO nanoparticles in hydroponics and soil Zinc accumulation increased significantly in roots, shoots and grains Lower dose of ZnO NPs (10 mg/L or mg/kg) augmented plant growth Antioxidant enzymes showed a significant increase in activity in ZnO NPs treatment GRAPHICAL ABSTRACT